A Concise Approach to Paxilline Indole Diterpenes - George, David T; Kuenstner, Eric J; Pronin, Sergey V (Journal of the American Chemical Society, 2015)
A synthetic approach to paxilline indole diterpenes is described. The route to the pentacyclic core relies on a new regioselective alkenylation of ketones and a tandem radical addition–aldol reaction sequence to access vicinal quaternary stereocenters. Emindole SB, the simplest member of the family, is synthesized in 11 steps from commercially available material to demonstrate the application of this approach.